Resolva a expressões numéricas a seguir: -8 + {-5 + [(8 – 12) + (13 + 12)] – 10} = *
sua resposta
Soluções para a tarefa
Respondido por
2
Resposta:
-2
Explicação passo-a-passo:
-8 + {-5 + [(8 – 12) + (13 + 12)] – 10} =
= -8 + {-5 + [-4 + 25] – 10} =
= -8 + {-5 + 21 – 10} =
= -8 + 6 =
= -2
Respondido por
1
Resposta:
-2
Explicação passo-a-passo:
-8 + {-5 + [-4 + 25] - 10}
-8 + {-5 + 21 - 10}
-8 + 6 = -2
Perguntas interessantes
Matemática,
7 meses atrás
Inglês,
7 meses atrás
Sociologia,
7 meses atrás
Biologia,
9 meses atrás
Matemática,
9 meses atrás
Psicologia,
1 ano atrás
Sociologia,
1 ano atrás